ANALISIS BIBLIOMETRIK PENGGUNAAN TIK DALAM PAI (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
The rapid development of information and communication technology (ICT) occurs in all fields, including Islamic Education (PAI). The learning process of PAI must continue to adapt to the development of ICT so that learning remains relevant and effective. This study was designed to (1) find out which literature has the highest number of citations; and (2) find out the trend of ICT usage in PAI. The method used was bibliometric analysis with VOSViewer application. The research data was collected from scientific research publications through the Google Scholar database with a search on Harzing's Publish or Perish (PoP) application in the period 2019-2024. Searching for key words in the title and abstract of the research resulted in 134 relevant published literature. The results showed that research using ICT in PAI as theme was most researched in 2022. R Rubiantica is the author with the highest citation which is 259 under the title ‘Interactive Learning Media Lectora Inspire as A Learning Innovation’ that was published in 2021. Topics that are rarely discussed apart from keywords are related to benefits, PAI teachers, and elementary schools. The limitations of this study only take the database on publications from Google Scholar within period 2019-2024 and the search results in PoP are limited to 200 literatures. Other national and international databases were not taken into account in this study.